A sourcebook on naturalist theatre - Innes, C. D. (Routledge, 2000)
This work aims to provide primary sources which document one of the key movements in modern theatre. It uses three writers to exemplify the movement, and six plays in particular, from Henrik Ibsen, Anton Chekhov, and George Bernard Shaw.